1994
DOI: 10.2134/agronj1994.00021962008600050010x
|View full text |Cite
|
Sign up to set email alerts
|

Feed Value of Forage Maize Hybrids Varying in Tolerance to Plant Density

Abstract: The yield response of forage maize (Zea mays L.) genotypes to plant density is not as clear as for grain hybrids, where density tolerant and sensitive types have been identified. A study including field trials, laboratory analyses, and in situ digestibility tests with one density‐tolerant and one sensitive hybrid was conducted with plant densities of 4 to 16 plants m−2. The investigations concentrated on stover. There are differences in sensitivity to planting density in forage maize yield. Differences between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 16 publications
2
14
0
1
Order By: Relevance
“…Pioneer 3902 achieved a maximum yield at 86800 plants ha −1 and declined as plant density increased further, while dry matter yield of Pioneer 3921 increased through the entire range of plant density treatments. Plant density × hybrid interactions for dry matter yield have been observed previously by Graybill et al (1991), Cox (1996), and Pinter et al (1994) A plant density × hybrid interaction was observed for ADF in the southern zone.…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…Pioneer 3902 achieved a maximum yield at 86800 plants ha −1 and declined as plant density increased further, while dry matter yield of Pioneer 3921 increased through the entire range of plant density treatments. Plant density × hybrid interactions for dry matter yield have been observed previously by Graybill et al (1991), Cox (1996), and Pinter et al (1994) A plant density × hybrid interaction was observed for ADF in the southern zone.…”
Section: Resultssupporting
confidence: 72%
“…Corn hybrids respond differently to high plant density (Phipps and Weller, 1979; Pinter et al, 1994). Nafziger (1994) suggested that newer hybrids have greater grain yield at higher plant densities than older hybrids.…”
mentioning
confidence: 99%
“…These results agree with the findings of Graybill et al (1991) and Widdicombe and Thelen (2002) who found that plant density did not have a significant effect on HI. However, Pinter et al (1994) reported that corn hybrids responded differently to high plant density. The effect of hybrid, row spacing and hybrid × row spacing interaction on the DM yield is shown in Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…It was determined that dry matter yields ranged from 11,371 kg/ha to 12,062 kg/ha in the averages of years according to intrarow spacing, while dry matter yield increased as intrarow spacing increased. Konak (1994) and Pinter et al (1994) found that the increase in plant density led to a decrease in dry matter rate and dry matter yield in their studies. The effects of silage corn varieties on dry matter yield were statistically significant according to the average of years (Table 5).…”
Section: Dry Matter Yieldmentioning
confidence: 96%